"When everyone is responsible, no one takes responsibility": exploring pediatric physiotherapy services in Israel - Nilly Waiserberg; Tuvia Horev; Paula Feder-Bubis (BMC, 2024)
Abstract Background According to Israel's National Health Insurance Law (1994), the Ministry of Health is responsible for the provision of health services in the country including physiotherapy services; moreover, the Special Education Law (1988), stipulates that physiotherapy services for children with motor disabilities, as well as other allied health services, are provided by the Ministry of Education in educational settings. Thus, children with motor disabilities are entitled PT services under two different laws by two different ministries. Method To describe the physiotherapy services for children with motor disabilities and examine how policymakers view these services, we conducted a qualitative study including in-depth semi-structured interviews with 10 policymakers from the Ministry of Health and the Ministry of Education, and the national directors of physiotherapy services from three of the four health maintenance organizations in Israel. Results Study results indicate that there is an array of physiotherapy services and providers. Despite the regulation of these services for children with motor disabilities, uncertainty and lack of knowledge were found about various issues. Therefore, the thematic analysis was structured around four descriptive questions: Where do the children receive physiotherapy? Who is eligible for physiotherapy treatment and who receives treatment? What interventions do children with motor disabilities receive? Who provides therapy for children with motor disabilities? Conclusions Policymakers are dubious regarding the provision of these services, questioning whether children with motor disabilities receive physiotherapy services according to their needs. In addition, the abundance of suppliers does not necessarily improve the quality of services provided to children with motor disabilities, which may ultimately harm their developmental potential.